The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1189/jlb.0607390
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic diet-induced hepatitis is partially dependent on murine TLR4

Abstract: Diets high in cholesterol and cholate such as the Paigen diet have been used to study atherogenesis, lithogenesis, and proinflammatory microvascular changes induced by nutritional hypercholesterolemia. Although these diets lead to chronic hepatic inflammation and fibrosis, the early inflammatory changes have been poorly characterized. TLR4, a known receptor for LPS, is also a receptor for a variety of endogenous ligands and has been implicated in atheroma formation. Here, we specifically examined the early inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 52 publications
9
32
1
1
Order By: Relevance
“…Thus, CE rather than TAG can be assumed to be a predominant pathogenic factor for the formation of fatty liver in our experimental models. Furthermore, similar pathological responses have been shown in the mice fed diets supplemented with CA and high levels of fats (Desai et al, 2008;Jeong et al, 2005), in which lipid-accumulation-mediated inflammatory responses were suggested to play an important role. Therefore, to better understand the pathogenesis of CA-induced fatty liver injury in the mice, we should further investigate the mechanism by which MUFA-containing CE accumulated in the liver contribute to the onset of inflammatory events in the liver.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, CE rather than TAG can be assumed to be a predominant pathogenic factor for the formation of fatty liver in our experimental models. Furthermore, similar pathological responses have been shown in the mice fed diets supplemented with CA and high levels of fats (Desai et al, 2008;Jeong et al, 2005), in which lipid-accumulation-mediated inflammatory responses were suggested to play an important role. Therefore, to better understand the pathogenesis of CA-induced fatty liver injury in the mice, we should further investigate the mechanism by which MUFA-containing CE accumulated in the liver contribute to the onset of inflammatory events in the liver.…”
Section: Discussionsupporting
confidence: 70%
“…This observation is inconsistent with previous reports from our laboratory 7 and by others. 25 While an explanation for the inconsistency is not readily apparent, it may result from the presence or absence of cholate in the cholesterol-enriched diet used in the different studies. Dietary cholate has been previously shown to induce inflammation and to potentiate the inflammation induced by a high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of TLRs has been described in apoEϪ/Ϫ mice and in human carotid atherosclerotic plaques. 24 Recently, it has been shown that a cholate-containing HFD induces an early inflammatory response that is mediated through TLR4 25 and that high-fat meals induce low-grade endotoxemia in humans and mice. 12,26 An increased serum concentration of IL-4 might be a factor that directly initiates MGC formation because this cytokine is required for the formation of FBMGCs in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%